Options for improving the communication of seasonal rainfall forecasts to smallholder farmers: the case of Kenya - Parita Shah; Chinwe Ifejika Speranza; Romanus Opiyo; Joshua Ngaina (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Africa is on the move! African countries and societies are advancing along various development paths. For some, Africa is the “booming continent” of our times. For others, it is home to the majority of the “bottom billion”. In the DIE's Briefing Paper series on African Developments, researchers from Europe and Africa regularly examine the African agenda and analyse African trends with a view to taking stock and identifying the challenges that will face the continent in the years to come. This ,,Briefing Paper“ discusses options for improving the communication of seasonal rainfall forecasts to smallholder farmers, taking Kenya as its example. Smallholder farmers depend on rain-fed agriculture in most of sub-Saharan Africa. Over time, they have adjusted their planting patterns and farming calendar to the onset, duration and end of the rainy seasons. However, with changing rainfall due to climate change, their planting patterns and farming calendar no longer match seasonal rainfall distributions, which often leads to crop losses. Seasonal rainfall forecasts are thus crucial for the provision of early warning information and, if used by farmers, can enable them to adjust their planting seasons and farming calendar. Yet farmers are often undecided whether to follow the recommendations of weather forecasts. As studies in Kenya show, this is due to uncertainty about their reliability, the limited ability of many farmers to comprehend the technical language used by meteorologists and the lack of access to detailed forecast information. Key actors in the communication of seasonal weather forecasts to farmers include the Kenya Meteorological Department (KMD), the Ministry of Agriculture (MoA), the Ministry of Livestock Development (MLD), the Ministry of Information and Communication and the media. These actors are beginning to address some of the challenges, but they should step up their efforts: The KMD needs to further downscale seasonal forecasts spatially to locally homogeneous rainfall zones or to weather-station level so that small-scale local variations in rainfall patterns can be taken into account. This would provide farmers with better information on their local rainfall patterns. The MoA and MLD should institutionalise their role in guiding the KMD in the communication of forecasts to farmers and pastoralists. As the climate information needs of smallholders are not adequately addressed by the KMD, this demand-driven approach recently adopted by the ministries as a pilot scheme may increase the influence of the agricultural sector on the design and content of forecasts and should therefore be continued. In collaboration with the KMD and the Ministry of Information and Communication, the MoA and MLD should explore the use of telephone short message services to complement existing radio services for the communication of ready-to-use forecasts. The MoA and MLD should hold pre-season forecast workshops at which county agricultural extension officers and officials of local meteorological stations can discuss downscaled seasonal forecasts and the implications for local agricultural production with farmers. Such local-level partnerships and facilitated farmergroup interactions can influence the strategies pursued by farmers in response to forecasts. Through these interventions, smallholder farmers are likely to regain confidence in seasonal forecasts and use them in agricultural production.
Keywords: 330; Klimawandel; Landwirtschaft und ländliche Entwicklung; Technologie und Innovation